Incidencia de la recaudación tributaria sobre el gasto en las funciones de planeamiento y de protección ambiental en la Municipalidad Distrital de Belén, periodo 2015 - 2020 - Hidalgo del Águila, Efren Abel (2022)
Tax collection in any type of economy represents the main source of financing for the adequate development of public functions that are carried out by the State, such as actions for economic stabilization, resource allocation and income redistribution. In this way, the question to be solved in this thesis is raised, which is shaped by investigating the hypothetical incidence of tax collection in the Belén district on public spending on planning and environmental protection functions in the District Municipality of Belén during the period 2015 - 2020. In this work it is determined that there is a direct incidence of tax collection on public spending in the detailed functions since, through the approach and estimation of a linear regression econometric model, it is obtained that the coefficient in charge of capturing the incidence of collection on public spending is 0.33, which means that if tax collection increases by 1 percent, spending on the aforementioned functions will increase by 33 percent; additionally, a Pearson correlation coefficient of 17.66 percent was obtained, which corroborates the presence of a positive relationship between the study variables.